Sliding Mode Control Strategy for Three-Phase DVR Employing Twelve-Switch Voltage Source Converter - Biricik, Samet; Komurcugil, Hasan; Basu, Malabika (IEEE, 2015)
In this study, a new method is proposed for the suppression of voltage amplitude fluctuations on the load terminals. Moreover, the voltage harmonics on the load terminals are effectively reduced below the defined limits in the IEEE-519 standard. In the studied topology, a twelve-switch three-phase voltage source converter is used for effective control on the zero-sequence components due to the unbalanced voltages or single phase voltage sags. In order to obtain a fast dynamic response, sliding mode control strategy is used to control the system. The existence condition of the sliding mode is presented. The performance of the closed-loop system is verified with cases of voltage sag and utility voltage harmonics. The overall system is explained in detail and verified by using MATLAB/Simulink.
41st Annual Conference of the IEEE-Industrial-Electronics-Society (IECON) -- NOV 09-12, 2015 -- Yokohama, JAPAN
Keywords: DVR; voltage sag; voltage harmonics; SOGI; sliding mode controller